Nature and nurture in the intergenerational transmission of socioeconomic status evidence from Swedish children and their biological and rearing parents - Björklund, Anders 1950-; Jäntti, Markus; Solon, Gary 1954- (Working paper series / National Bureau of Economic Research, 2007)
This study uses an extraordinary Swedish data set to explore the sources of the intergenerational transmission of socioeconomic status. Merging data from administrative sources and censuses, we investigate the association between sons' and daughters' socioeconomic outcomes and those of their biological and rearing parents. Our analysis focuses on children raised in six different family circumstances: raised by both biological parents, raised by the biological mother without a stepfather, raised by the biological mother with a stepfather, raised by the biological father without a stepmother, raised by the biological father with a stepmother, and raised by two adoptive parents. Relative to the existing literature, the most remarkable feature of our data set is that it contains information on the biological parents even when they are not the rearing parents. We specify a simple additive model of pre-birth (including genetic) and post-birth influences and examine the model's ability to provide a unified account of the intergenerational associations in all six family types. Our results suggest substantial roles for both pre-birth and post-birth factors.